ANALISIS FAKTOR PENENTU NIAT BERWIRAUSAHA MAHASISWA UNIVERSITAS SEBELAS MARET - Asri Laksmi Riani; Heru Irianto; Agus Widodo (KINERJA, 2013)
The objective of research is to fi nd out the determinant factor of Student Entrepreneurship Intention inSebelas Maret University (UNS) and how such the factors interrelated, so that it is expected that from thisresearch there will be found further development of entrepreneurship education program toward the creationof entrepreneur from the campus that in turn will encourage the nation’s progress and competitiveness. Thenumber of sample was determined by individual faculties consisting of 35 respondents, with the total sample of315 respondents, so that it met the data feasibility minimum criteria with structural equation model (SEM).The result of research shows that the subjective norm (family or friend), positive attitude to entrepreneurshipand UNS’s institutional support are the determinant factors supporting the UNS’s student intention to haveentrepreneurship. The implication of research in the future is that there should be classifi cation among thebusiness and non-business students; and geographical coverage expansion between the university withinindustrial area and that far from industrial area.Keywords: Subjective norm, attitude, intention, having entrepreneurship, students